¿Qué hay en los nombres de los vigilantes henóquicos? Aproximación a su función - Hernández-Valencia, Juan Sebastián (Teología y vida, 2025)
Although the philological study of the names of the Twenty Enochic Watchers and their manuscript tradition has reached a certain well grounded point, as far as the existing sources permited it, there is still a study to do of their function and significance within the mythical narrative systems that transmit them. This article aims to offer an approach to such a study. First, returning to the works of Milik, Knibb Schmidt and Langlois, a synthesis of the philological problems will be developed in relation to the information available on the current state of the story about the Watchers in the manuscript tradition, especially the two lists of Watchers that are in 1 En 6:7 and 1 En 69:2. In a second moment, a synchronous study will be undertaken, classifying and analyzing the material according to a thematic criteria. The article will defend the idea about an adaptation of the astrological divinities of the Canaanite and Sumerian Pantheon, used to develop a critique of the possible social and political conflicts of Second Temple Judaism through language and mythological imagery.